Assessing the long-term effects of microbial therapeutics as treatment within psychiatry: a systematic review - Sgarbossa, Cassandra; Chinna Meyyappan, Arthi; Forth, Evan; Bromley, Hayley; Milev, Roumen (Frontiers in Psychiatry, 2026)
BackgroundThe management and treatment of psychiatric disorders by manipulating the gut microbiome and utilizing microbial therapeutics, via modulation of the gut-brain-axis, has been a rapidly growing field of research. Given the novelty of using microbial therapeutics within psychiatry, a growing number of studies have investigated their use as treatment for various psychiatric disorders and symptoms. However, few studies have explored the longitudinal efficacy of these treatments. This review aims to summarize the findings of any studies assessing the long-term effects of gut-related interventions on mood and psychiatric symptoms.MethodsA systematic search of 4 databases (Embase, PsycINFO, Medline, Web of Science) from inception to May 28, 2025, informed by Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, and using key words relating to microbial therapeutics, psychiatric disorders, and long-term effects was conducted. Findings were included or excluded using pre-determined eligibility criteria such as being been written in English and published by a peer-reviewed journal, assessed for quality using the Cochrane Handbook for Systematic Reviews of Interventions Risk of Bias tool, and qualitatively evaluated.ResultsThe search yielded 4175 studies, of which 1274 duplicates were removed. All remaining studies underwent abstract screening, from which 70 records were full-text screened and a total of ten clinical studies (n = 10) met eligibility criteria and were included in the review. The majority of studies explored the effects of microbial therapeutics such as fecal microbiota transplant and probiotics, as treatment for disorders of the gastrointestinal tract as the primary scope, with additional outcome measures assessing psychiatric well-being. The review presented with mixed findings: many studies reported a sustained improvement in symptoms of depression and anxiety ranging from 3- to 18-months post-treatment, while others reported the opposite with no sustained long-term improvement in mood-related symptoms. There was also a lack of consistency across follow-up duration between studies, making it difficult to compare findings.ConclusionsOverall, this review highlighted the need for more placebo-controlled studies with larger sample sizes to effectively evaluate the longitudinal potential of microbial therapeutics as treatment for mood-disturbances and psychiatric symptoms. With consideration for the limitations of this field, these results provide evidence that there may be long-term benefits of targeting the gut microbiome as treatment for mood-related disturbances.